Empowerment of Watermelon Farmer at Mojosari Village Puger District Jember in Producing Watermelon Low Pesticide Residue - Nanang Tri Haryadi; Hari Purnomo; Titin Agustina (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Mojosari Village, Puger Sub-district, is the largest watermelon center in Jember Regency. In 2017, the total harvested area reached 900 Ha and productivity reached 290.72 kW / Ha. The problem that often arises in watermelon cultivation is the attack of plant pests. Pests that often attack watermelons include caterpillars, whitefly, fruit flies, and thrips. Pest control that is often used by farmers is sprayed with chemical pesticides. The spraying of chemical pesticides began to be complained about by farmers because they were not able to control pests, this was probably because the pests were already resistant to pesticides. The decline in watermelon quality is also caused by soil conditions that have begun to decrease in nutrient content, due to the use of excessive chemical fertilizers. Farmers become dependent on chemical pesticides and chemical fertilizers in watermelon cultivation. Therefore, it is necessary to educate farmers to reduce the use of excessive chemical pesticides and fertilizers. One alternative is to use environmentally friendly biological control agents. The result of this activity is that farmers can reproduce biological agents, namely the fungus Metarhizium anisopliae, Beauveria bassiana, Trichoderma, entomopathogenic nematodes, and make organic fertilizers. Farmers can produce biological agents and apply them to watermelon fields. The resulting watermelon is more durable to store and does not rot easily after harvest.